Early and late effects of radiochemotherapy on cerebral blood flow in glioblastoma patients measured with non-invasive perfusion MRI. Issue 1 (January 2016) - Petr, Jan; Platzek, Ivan; Seidlitz, Annekatrin; Mutsaerts, Henri J.M.M.; Hofheinz, Frank; Schramm, Georg; Maus, Jens; Beuthien-Baumann, Bettina; Krause, Mechthild; van den Hoff, Jörg
Abstract: Background and purpose: To provide a systematic measure of changes of brain perfusion in healthy tissue following a fractionated radiotherapy of brain tumors. Materials and methods: Perfusion was assessed before and after radiochemotherapy using arterial spin labeling in a group of 24 patients (mean age 54.3 ± 14.1 years) with glioblastoma multiforme. Mean relative perfusion change in gray matter in the hemisphere contralateral to the tumor was obtained for the whole hemisphere and also for six regions created by thresholding the individual dose maps at 10 Gy steps. Results: A significant decrease of perfusion of −9.8 ± 20.9% ( p = 0.032) compared to the pre-treatment baseline was observed 3 months after the end of radiotherapy. The decrease was more pronounced for high-dose regions above 50 Gy (−16.8 ± 21.0%, p = 0.0014) than for low-dose regions below 10 Gy (−2.3 ± 20.0%, p = 0.54). No further significant decrease compared to the post-treatment baseline was observed 6 months (−0.4 ± 18.4%, p = 0.94) and 9 months (2.0 ± 15.4%, p = 0.74) after the end of radiotherapy. Conclusions: Perfusion decreased significantly during the course of radiochemotherapy. The decrease was higher in regions receiving a higher dose of radiation. This suggests that the perfusion decrease is at least partly caused by radiotherapy. Our results suggest that the detrimental effects of radiochemotherapy on perfusion occur early rather than later.